2019
DOI: 10.1007/s00125-019-4866-5
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of long-term exercise on plasma adipokine levels and inflammation-related gene expression in subcutaneous adipose tissue in sedentary dysglycaemic, overweight men and sedentary normoglycaemic men of healthy weight

Abstract: Aims/hypothesis Obesity and insulin resistance may be associated with altered expression and secretion of adipokines. Physical activity can markedly improve insulin sensitivity, but the association with adipokines remains largely unknown. In this study, we examined the effects of physical activity on the subcutaneous white adipose tissue (scWAT) secretome and its relationship to insulin sensitivity. Methods As reported previously, we enrolled 26 sedentary, middle-aged men (13 dysglycaemic and overweight; 13 no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
35
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 51 publications
1
35
0
Order By: Relevance
“…Several studies have shown that a high level of fitness (defined by a high activity level with maximal oxygen uptake) negatively associates with visceral adiposity (506)(507)(508), even in subjects with obesity and/or T2DM, suggesting that aerobic exercise contributes to a favorable adipose distribution profile that reduces the risk of metabolic syndrome. Hepatic fat is also mobilized and decreased following intense aerobic exercise (509). Studies in mice suggest that not only visceral fat mass is lost with regular exercise, but subcutaneous and brown fat mass are also diminished (510).…”
Section: Lifestyle Modifications: Including Exercisementioning
confidence: 99%
“…Several studies have shown that a high level of fitness (defined by a high activity level with maximal oxygen uptake) negatively associates with visceral adiposity (506)(507)(508), even in subjects with obesity and/or T2DM, suggesting that aerobic exercise contributes to a favorable adipose distribution profile that reduces the risk of metabolic syndrome. Hepatic fat is also mobilized and decreased following intense aerobic exercise (509). Studies in mice suggest that not only visceral fat mass is lost with regular exercise, but subcutaneous and brown fat mass are also diminished (510).…”
Section: Lifestyle Modifications: Including Exercisementioning
confidence: 99%
“…Exercise and lifestyle modifications lower the mortality risk, improve quality of life and have been extensively studied. Physical activity improves insulin sensitivity and alters AT adipokine expression, which affect whole-body metabolic health in human subjects (512,513). Recent studies highlighted the mechanistic pathways, linking those two interventions with decreasing AT inflammation.…”
Section: Exercise and Lifestyle Modificationsmentioning
confidence: 99%
“…Zielger et al demonstrated that exercise enhances the antiinflammatory phenotype in VATs of old mice (517). Endurance training regardless of weight loss induced an increase in M2 macrophages in scWAT (513,518). The role of physical activity in thermogenesis and WAT browning is debated as some reported scWAT browning with bicycle training programs while another study failed to find a correlation between aerobic exercises and recruitment of beige adipocytes (519,520).…”
Section: Exercise and Lifestyle Modificationsmentioning
confidence: 99%
“…Previous animal and human studies have shown that regular exercise training has beneficial effects on adipose tissue. Regular exercise training has been shown, both in subcutaneous adipose tissue (SAT) and visceral adipose tissue (VAT), to reduce adipose tissue mass, 4 5 adipocyte hypertrophy, adipose tissue inflammation 6 and increase mitochondrial function and biogenesis 7 in humans and rodents. A recent study showed that exercise training influences (increase/decrease) global expression of inflammation-related factors especially in abdominal SAT especially in dysglycemic men.…”
Section: Introductionmentioning
confidence: 99%